Temperature-tunable topological zero-refraction acoustic metamaterials - Chu, Yangyang; Sun, Tong; Wang, Zhaohong; Zhang, Zhifeng (Frontiers in Materials, 2024)
Zero-refractive index metamaterials have a wide range of applications in directional transmission and wave-front shaping due to their unusual acoustic properties. However, for most given acoustic topological metamaterials, the operating frequency is relatively fixed and the effect of temperature on their topological properties is rarely considered. Therefore, temperature-controlled tunable topological zero-refraction acoustic metamaterials are proposed in this paper. Firstly, a metamaterial with quadruple degenerate Dirac-like points at the center of the Brillouin zone is constructed. By adjusting the structural parameters, the degenerate Dirac cones can be opened to form a topological bandgap, and the effect of temperature on the topological bandgap is analyzed. Pseudospin-polarized edge states are obtained at the interface of two phononic crystals with different topological phases. The topological zero-refraction property of the edge states outcoupled into free space is numerically demonstrated, and the non-contact active control of their operating frequencies can be realized by temperature. This study can provide a corresponding reference for the intelligent control of near-zero refractive index acoustic topological materials in elastic wave collimation and acoustic communication.